Website Pintar Untuk Diet Harian Dengan Menggunakan Metode Fuzzy Tsukamoto - I Made Harma Sastra; A.A. Ayu Putri Ardyanti; I Nyoman Purnama; Ketut Queena Fredlina (Institut Bakti Nusantara, 2023)
Food is the main factor to support the body in carrying out various activities. Balance in consuming food plays a very important role for health, too much consumption of the same type of food without balancing it with other foods can lead to things that can trigger various diseases such as diabetes, high blood pressure, cholesterol, and so on. The purpose of this research is to calculate the level of daily calorie requirements for people who are on a daily diet. The method used is the fuzzy tsukamoto method in calculating daily calories where there is a division of time for meal portions according to daily calories, for example breakfast, lunch, dinner. Research results using a case study of age: 25 years old, weight: 170kg, height: 165cm, gender: female, activity: retirement. From the case study get the results of 1279 calories and the division of calories according to time, breakfast: 256 calories, snack: 160 calories, lunch: 384 calories, snack: 160 calories, dinner: 320 calories.